Authority for the Development and Supervision of Regional Legal Products from Regional Autonomy Perspective - Sy Masyithah; Faisal A Rani (Kanun Jurnal Ilmu Hukum, 2021)
Law Number 23 of 2014 requires local governments to obtain a register number in the formation of the Perda (regional regulation) as part of supervision. Furthermore, Law Number 15 Year 2019 requires Regional Governments to harmonize, unify, and implement conceptions of the formation of Regional Regulations as part of coaching. In the context of regional autonomy, the constitution gives authority to the regions to regulate and manage government affairs by themselves according to the principles of autonomy and duty of assistance as well as to carry out the broadest possible autonomy. The research aims to study and explain the methods and stages used by the central government in fostering and supervising regional legal products from the perspective of autonomy and their material boundaries. The method used in this research is normative legal research method.harmonizing, rounding off and stabilizing conception. While supervision by giving register numbers, clarifications, and cancellations.The limitation of guidance and supervision material is based on the category of legal products classified as facilitation or evaluation.